Time and frequency domain analysis of ground reaction forces in jumping with elite rhytmic gymnasts - Torrents, C.; Ferro, A.; Balagué, N.; Ferreruela, M.; Floira, P.; Rivera, A. (International Journal of Computer Science in Sport, 2002)
Testing in sport is based traditionally in evaluation of states and discrete parameters instead of processes and changes in the evolution of performance. Introduction of tools from dynamical systems in sport research has opened new ways of testing and interpreting data. These tools have mainly been used in sport for modelling rhythmic cyclic movements and analysing the phenomena of human coordination (Kelso, 1995). However they can also be used for analysing non-cyclic movements and the behaviour of the athlete performing technical exercises. Frequency domain analysis of time series, that has been used to study gait patterns, can help us to study the variations and features of the shape of force records. The aim of this study is to study the fluctuations of the time series of ground reaction forces during jumps of rhythmic gymnasts using the frequency domain analysis in order to identify individual patterns and changes with training (instead of the more commonly applied statistical analysis of discrete variables).